Acute Lymphoblastic Leukemia in the Department of Child Health, School of Medicine, University of North Sumatera/ Dr. Pirngadi Hospital Medan (1980 - 1988) - Zairul Arifin; Feraluna Nasution; Adi Sutjipto (Indonesian Pediatric Society, 1991)
A retrospective study on acute lymphoblastic leukemia (ALL) was conducted to assess the pattern of childhood ALL at the Subdivision of Pediatric of Hematology, School of Medicine, University of North Sumatera/ Dr. Pirngadl Hospital, Medan, in a period of 8 years (1980 - 1988). There were 120 cases, consisting of 63 (51.5%) males and 57 (47.5%) females. By the FAB classification (Bennett, 1976; 77.5% ) were found as FAB L1, 25 (20.8%) as FAB L1, and 2 (1.7%) as FAB L 3. The youngest was 4 months old. The majority of signs and symptoms appeared In the forms of pallor 102 (85%), fever 84 (70%), hemorrhage 52 (43.3%), hepatomegaly 64 (53.3%), splenomegaly 54 (45%) and lymphadenopathy 18 (15%). On first admission, 76 (63.33%) cases were with a leukocyte count of less than 20,000/ ul, and 72 (60%) with Hb content of less than 5 g/dl. Twenty one cases died In the first year. The received cytostatic protocol; 11 (S2.38'1o) were treated regularly and first remission were found in 8 (72. 73%) cases. The average of admissions per year for the age group of 2Â·8 years was higher than the age groups of 0Â·2 years and 8-16 years (p < 0.05).